Evangelical gothic : the English novel and the religious war on virtue from Wesley to Dracula - Herbert, Christopher, 1941- (Victorian literature and culture series., 2019)
"Examining both the theology of John Wesley, George Whitefield, and William Wilberforce and novels by Charles Dickens, George Eliot, Sir Walter Scott, and Bram Stoker as well as a host of 'Evangelical novels' of the period, Herbert analyzes the Evangelical and anti-Evangelical forces at play in Victorian literature and culture, challenging accepted notions of the impact of the Evangelical movement on gothic Victorian literature."--